May a hybridogenetic complex regenerate the nuclear genome of both sexes of a missing ancestor? First evidence on the occurrence of a nuclear non-hybrid Squalius alburnoides (Cyprinidae) female based on DNA sequencing - Santos, Carla Sousa (2013)
Based on molecular evidence and on direct observation of gonads and morphology, we describe the occurrence of a female of the hybridogenetic minnow Squalius alburnoides bearing the nuclear genome of the paternal ancestor of the complex and the mtDNA of S. pyrenaicus (the maternal species). The paternal ancestor is believed to be extinct and the available molecular evidence indicates that it was a species distant from the maternal ancestor and closer to a very different genus (Anaecypris). Its nuclear genes were perpetuated through hybrids and through diploid males originated from the hybrids and containing two copies of the paternal genome. The discovery of a diploid female with the pure nuclear genome of the paternal ancestor, even if it represents a very rare occurrence, illustrates a very interesting biological phenomenon: the possibility of re-emergence of an extinct species from its descendent hybrids, although carrying the mtDNA of another species.